Analysis of the Implementation of Accounting Information Systems on Individual Performance, Organizational Performance, and Net Benefits - Arista Arya Ismaya; Gusti Ayu Putu Eka Dewi Prihantari (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The development of information technology has encouraged business actors, including small enterprises in the food and beverage sector, to adopt Accounting Information Systems (AIS) to support financial and operational management. Selesa Coffee & Eatery, as a small enterprise, has implemented ESB POS (Esensi Solusi Buana Point of Sales) to facilitate transaction recording and financial report management. This study aims to analyze the impact of implementing an ESB POS–based AIS on individual performance, organizational performance, and net benefits using the DeLone & McLean (2003) model framework. The research employed a qualitative approach with a case study strategy. Data were collected through interviews with managers and accounting staff, direct observation of the café’s operational activities, and documentation of system-generated financial reports. Data analysis was conducted using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing, along with triangulation to validate the findings. The results show that the implementation of ESB POS enhances individual performance by simplifying record-keeping, accelerating reporting, and reducing manual errors. At the organizational level, the system supports operational efficiency, transparency, and work coordination. In terms of net benefits, the system contributes to improved data accuracy, time efficiency, and provides support for evaluation and strategic decision-making. This study concludes that the implementation of an ESB POS–based AIS significantly contributes to the sustainability of small enterprises.